Analisis Sistem Informasi Akuntansi pada Pengelolaan Zakat di Badan Amil Zakat Nasional (Baznas) Kota Binjai - Cindy Purnama Asry Nasution; Yenni Samri Juliati Nasution (Universitas Muhammadiyah Surabaya, 2023)
AbstractThe purpose of this study was to determine the Implementation of Accounting Information Systems in Zakat Management at the National Amil Zakat Agency (BAZNAS) in Binjai City. The type of research used in this research is descriptive research with a qualitative research approach. The results of this study explain that the management system of the Amil Zakat Agency in Binjai City has carried out its duties and functions as the Amil Zakat Agency which collects zakat, infaq and alms funds very well and optimally as regulated in Law no. 23 of 2011. As for the recording of financial reports, BAZNAS for Binjai City has not yet prepared its financial reports in accordance with the zakat accounting system, namely PSAK 109.Keywords: Accounting, Zakat, BAZNAS